Cis-12-Oxo-phytodienoic acid represses Arabidopsis seed germination in shade conditions. (20th July 2019) - Barros-Galvão, Thiago; Dave, Anuja; Cole, Adama; Harvey, David; Langer, Swen; Larson, Tony R; Vaistij, Fabián E; Graham, Ian A
Abstract : cis -12-Oxo-phytodienoic acid acts in addition to ABA to repress seed germination under far-red light conditions. The response to both these phytohormones is integrated by MFT, a negative regulator of germination. Abstract: Light-dependent seed germination is induced by gibberellins (GA) and inhibited by abscisic acid (ABA). The widely accepted view of the GA/ABA ratio controlling germination does not, however, explain the fact that seeds deficient in ABA still germinate poorly under shade conditions that repress germination. In Arabidopsis, MOTHER-OF-FT-AND-TFL1 (MFT) acts as a key negative regulator of germination, modulating GA and ABA responses under shade conditions. Under full light the oxylipin cis -12-oxo-phytodienoic acid (OPDA), a precursor of the stress-related phytohormone jasmonic acid, interacts with ABA and MFT to repress germination. Here, we show that under shade conditions both OPDA and ABA repress germination to varying extents. We demonstrate that the level of shade-induced MFT expression influences the ability of OPDA and/or ABA to fully repress germination. We also found that MFT expression decreases with seed age and this again correlates with the response of seeds to OPDA and ABA. We conclude that OPDA plays an essential role alongside ABA in repressing germination in response to shade and the combined effect of these phytohormones is integrated to a significant extent through MFT .